State, Civil Society and Expanding Social and Solidarity Economy among Informal Sector Women in Ethiopia - Ossome, Lyn (UNRISD Conference on Potential and Limits of Social and Solidarity Economy, 2013)
The paper draws from empirical evidence gathered in Addis Ababa, Ethiopia from April-May 2012, during field research to investigate the social and political dynamics of women’s community activism there.1 It examines the ways in which women engaged in informal sector work are being organised under savings and credit cooperatives (SACCOs), and through this critique, investigates the potential for expanding social and solidarity economy (SSE) through savings and credit cooperatives. The guiding hypothesis is that the political economy of policy changes in Ethiopia under which the savings and credit cooperatives are being formed delimits the possibility of expanding SSE through this method. Women in Addis Ababa are involved in many forms of informal sector work, most of which offer minimum wage, is dangerous at times, and most importantly, has failed to significantly lift them out of poverty. At the same time, however, women’s organisations in Addis Ababa have shown remarkable initiative with regards to mobilizing women around savings and cooperative schemes aimed at mobilizing women to save and regenerate their own incomes. These schemes enjoy a broad reach, and include women working as coffee sellers, weavers, street vendors, domestic workers, firewood carries, garbage collectors and even street beggars. There are a number of initiatives to empower women especially those that have no education and income, through savings, loans and income generating activities. Many are organized under self-help groups and cooperatives, which not only have economic objectives but also play an important social and cultural role in bringing together women who previously would not work together due to cultural discrimination and stigma around certain work, like garbage collection, which are identified with a lower caste.